Effect of Model Drawing Strategy for Fraction Word Problem Solving for Students with Learning Disabilities - Al-salahat, Mohammad; Saleem, Suhib (Dirasat: Educational Sciences, 2020)
The present study aims to investigate the impact of drawing strategy on mathematical fraction word problem solving among a group of students with learning disabilities. The study adopted the quasi-experimental single subject design, and involved (6) intentionally selected students with learning disabilities in the fourth primary grade at on of the primary school in Najran, Saudi Arabia. It developed and applied a 12-item test with word problems mathematical fraction. It also utilized a model with clear instructions for using pictograms to solve word problems mathematical fraction. The results pointed out that the poroposed interventional strategy was effective in improving mathematical fraction word problem solving among participant students with learning disabilities. The researhers encourage teachers from that particular school to expand the usage of the drawing strategy while paning and teaching mathematical fraction word problems, and provide other teachers of students with learning disabilities from other schools with training on using the proposed strategy.